Minimizing equipment shutdowns in oil and gas campaign maintenance. Issue 7 (12th July 2021) - Seif, Z.; Mardaneh, E.; Loxton, R.; Lockwood, A.
Abstract: This paper considers the problem of scheduling periodic maintenance items for oil and gas plants. Each maintenance item involves various maintenance tasks and may require temporary equipment shutdowns, which are costly and highly disruptive to production. The aim is to minimise equipment shutdowns by grouping maintenance items with similar shutdown requirements into short-term maintenance operations called campaigns. Real plants can involve tens of thousands of maintenance items and thus manually scheduling the campaigns is an extreme challenge. In this paper, we develop a mixed-integer linear programming model for optimally allocating maintenance items to campaigns so that total shutdown cost is minimised. The model incorporates constraints on maintenance deadlines, campaign times, maintenance item suppression and labour hours per campaign. We solve the model for realistic scenarios involving data for Karratha Gas Plant in Western Australia, which is the main processing plant for the massive North West Shelf oil and gas project.